The Role of Civil Society Organizations in promoting Peace and Economic Development - Nso, Maurice Ayuketang (Asian Journal of Interdisciplinary Research, 2020)
Change is a fundamental human right. Without apparent change, nations struggle to advance economically. Change for peace to prevail is a contemplated philosophy from reality when sectors that stir peace are misaligned. Civil Society Organizations (CSOs) are the relevant third sector, yet the treatment of civil society by the first sector - the public sector - is indifferent. This study justifies civil society role in promoting peace and economic development. Counting diplomatic missions and multilateral agencies part in stirring peace and development, it recommends, collaborative, harmonious exchanges and relationships within the three sectors – public, private and the civil society – for the sake of proper peace and economic development for the wellbeing of citizens and nations. The study examined 41 individuals with familiarities in civil society were sampled. One-Way ANOVA technique was employed to test the hypotheses. The test results show significant associations between: economic advancement and peace; and CSOs actions in peace promotion and economic enhancement.